Fostering Quality Teaching in Higher Education Institutions - Salau, K. K.; Umaru, H. A. (International Journal of Educational Management, 2022)
Fostering quality teaching is sine qua non to achieving educational goals in any nation. Globally, education is a critical tool for social, economic and political development and these goals of education can be fully attained if quality teaching is available to students, especially in higher education institutions. Higher education of good quality is significant for Nigeria to become globally competitive. Thus, this article identified teacher-factors, inadequate funding, government factors, lack of resources, lack of information communication technology facilities, frequent labour disputes and closures of universities, lack of vibrant staff development programmes, and student factors serve as a clog in the wheel of attaining quality teaching in Nigerian higher education institutions. It is, therefore, recommended that Nigerian government should meet up with the 26 per cent education spending as recommended by UNESCO. Besides, reform in existing higher education institutions in Nigeria can be attained via collaborative efforts between government and other sectors of Nigerian economy.